2019
DOI: 10.4034/pboci.2019.191.76
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors of Biopsychosocial with Early Childhood Caries (ECC) in Indonesian Pre-School Children

Abstract: Objective: To describe the Early Childhood Caries (ECC) in Indonesian preschool children based on biopsychosocial risk factors. Material and Methods: This research is an analytic observational with a cross sectional design toward 506 preschool children aged 2-6 years at East Luwu Regency, Indonesia. The biopsychosocial data studied were gender, ethnicity, personal hygiene, child psychology, age, nutritional status, and dental and oral health behavior. These data were obtained through a questionnaire and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…shows the appropriate results that the ant nest has compounds that can inhibit bacterial growth. The results of this study also provide the same results that the use of ethanol solvents to extract active compounds in ant nests provides a zone of inhibition of tested bacteria [12][13][14].…”
Section: Discussionsupporting
confidence: 79%
“…shows the appropriate results that the ant nest has compounds that can inhibit bacterial growth. The results of this study also provide the same results that the use of ethanol solvents to extract active compounds in ant nests provides a zone of inhibition of tested bacteria [12][13][14].…”
Section: Discussionsupporting
confidence: 79%
“…The Javanese population, mostly from Central Java, is known to consume limited portions of food, especially staple foods, fruits, and vegetables compared with other ethnic groups in the country 28 . A previous cross-sectional study of dental caries among children in South Sulawesi found higher prevalence (more than 15%) of early childhood caries in the Bugis, Toraja, and Javanese ethnicities compared to that in another ethnicities 29 . Interestingly, the Toraja ethnicity showed the highest toothache prevalence in 2014 of 25.93%.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, they stated that healthy consumption patterns such as the Mediterranean-style diet offer a defensive effect against ECC; nevertheless, the fast-food-style Western diet brings about dental caries in children. According to Achmad et al 37 children who did not consume vegetables were more prone to ECC (77.9%), compared to children who consumed vegetables as a habit. Obradovic ´et al 47 found that higher meal frequency, having more than 8 meals per day was strongly correlated with the prevalence of S-ECC, according to cross-sectional observations.…”
Section: Eating Habits and Eccmentioning
confidence: 99%